Direct immersion solid‐phase microextraction with gas chromatography and mass spectrometry for the determination of specific biomarkers of human sweat in melted snow. Issue 7 (April 2016) - Dallo, Federico; Battistel, Dario; Piazza, Rossano; Gabrieli, Jacopo; Filippi, Jean‐Jacques; Baldovini, Nicolas; Barbante, Carlo
Abstract : To provide a reliable tool for investigating diffusion processes of the specific components of the human odor 3‐hydroxy‐3‐methylhexanoic acid and 3‐methyl‐3‐sulfanylhexan‐1‐ol through the snowpack, we developed and optimized an analytical method based on direct immersion solid‐phase microextraction followed by gas chromatography with mass spectrometry. Direct immersion solid‐phase microextraction was performed using polyacrylate fibers placed in aqueous solutions containing 3‐hydroxy‐3‐methylhexanoic acid and 3‐methyl‐3‐sulfanylhexan‐1‐ol. After optimization, absorption times of 120 min provided a good balance to shorten the analysis time and to obtain suitable amounts of extractable analytes. The extraction efficiency was improved by increasing the ionic strength of the solution. Although the absolute extraction efficiency ranged between 10 and 12% for 3‐hydroxy‐3‐methylhexanoic acid and 2–3% for 3‐methyl‐3‐sulfanylhexan‐1‐ol, this method was suitable for analyzing 3‐hydroxy‐3‐methylhexanoic acid and 3‐methyl‐3‐sulfanylhexan‐1‐ol concentrations of at least 0.04 and 0.20 ng/mL, respectively. The precision of the direct immersion solid‐phase microextraction method ranged between 8 and 16%. The variability within a batch of six fibers was 10–18%. The accuracy of the method provided values of 88–95 and 86–101% for 3‐hydroxy‐3‐methylhexanoic acid and 3‐methyl‐3‐sulfanylhexan‐1‐ol, respectively. The limit of detection (and quantification) was 0.01 ng/mL (0.04 ng/mL) for 3‐hydroxy‐3‐methylhexanoic acid and 0.06 ng/mL (0.20 ng/mL) for 3‐methyl‐3‐sulfanylhexan‐1‐ol. The signal versus concentration was linear for both compounds ( r 2 = 0.973–0.979). The stability of these two compounds showed that 3‐hydroxy‐3‐methylhexanoic acid was more stable in water than 3‐methyl‐3‐sulfanylhexan‐1‐ol. We applied the method to environmental samples in correspondence with an olfactory target buried previously.